Simulation of temperature distribution without products inside a clay pottery kiln at Dan Kwian, Thailand - Jongpluempiti, Jarinee; Tangchaichit, Kiatfa (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this study was to determine the temperature distribution in an empty clay pottery kiln at Dan Kwian kiln without products. Firewood was used as fuel, and then the results of temperature were referenced to uid dynamic calculation and analyzed by a nite element program. The sizing results for an element appropriate in this simulation was 100 millimeter and the velocity of the hot air ow into the kiln was 0.09 meters per second. The error of the temperature calculated from the actual experimental data was about 11.68 percent. This model can predict the temperature distribution and explain the phenomena of actual ow in a clay pottery kiln at Dan Kwian, Thailand.